The Use of E-Learning Platforms in University Teaching: Reality and Challenges A Field Study at the Faculty of Education in Zliten as a Model (Sebha University Conference Proceedings, 2025)
The current study aimed to identify the extent of the use of e-learning platforms in university teaching, explore the obstacles to their use, and determine the degree of awareness among faculty members at the Faculty of Education in Zliten regarding the importance of using e-learning platforms in teaching. To achieve these objectives, the study relied on the analytical descriptive approach and the questionnaire technique as a data collection tool. The questionnaire was applied to a sample of 35 faculty members at the Faculty of Education, Al-Asmariya Islamic University. The study concluded with several key findings, the most important of which are:Faculty members at the Faculty of Education in Zliten use e-learning platforms to a moderate degree due to shortcomings in the requirements for their use in aspects such as (planning, implementation, evaluation, and social communication). Additionally, faculty members have a high level of awareness regarding the importance of using e-learning platforms. However, they face significant obstacles in utilizing these platforms. The results did not show any significant differences among the faculty members in the study sample regarding their estimates of the degree of use and importance of e-learning platforms based on variables such as (gender, specialization, academic degree, years of experience, and training courses).